On the Endangered Species List: Are Secondary Reading Specialists Becoming Extinct? - Carolyn Carlson (The Advocate, 2011)
Research indicates a need for support for struggling readers at the secondary level, including access to reading specialists that can provide them with expert guidance and instruction to improve their reading skills. Minimal research has been conducted on reading specialists at the secondary level, so little is known about these teachers. Therefore, the purpose of this study was to examine the number of secondary reading specialists employed in public schools. Data from the National Center for Education Statistics were analyzed in this study and indicate that there is a strikingly small number of reading specialists employed at the secondary level. This study examines this and offers suggestions for future research in the area of secondary reading specialists.